PENGARUH UKURAN PERUSAHAAN, INTENSITAS ASET TETAP, PROFITABILITAS, DAN THIN CAPITALIZATION TERHADAP TAX AVOIDANCE - Sinaga, Gerika Uli; Sudarmaji, Eka; Astuti, Shinta Budi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
The phenomenon of decreasing taxes received has made the government's attention. In order to reduce the tax burden paid, there are several ways that taxpayers can, through tax avoidance or tax expansion. Corporations that carry out their operational activities in the territory of Indonesia are required to pay their tax burden to the state. A significant tax burden will reduce the profit received by the corporation. This study aimed to detect the effect of company size, fixed asset intensity, profitability, and thin capitalization. The population in this study was the manufacturing sector engaged in the basic and chemical industries. A total of 41 companies with 123 data were used in this study. The data used was obtained through the Indonesia Stock Exchange website. The data analysis technique was the panel data regression model, which was processed using the program eviews version 12. The results showed that company size did not affect tax avoidance, while fixed asset intensity, profitability, and thin capitalization had a negative effect on tax avoidance practices.